Vibration Modal Analysis of a New Type of Automobile Transmission Housing - Tao Xiaomin; Wang Shaojie (Jixie chuandong)
Based on the transmission housing which is designed independently by Automotive Engineering Technology Research Institute of Hefei University of Technology,the three- dimensional modeling of the housing is built by using Pro / E software,then imported in hypermesh saved as. DAT format after meshing. Then,the modeling is imported into the mechanical transmission system of the transmission which has already been established in the Romax Designer,and the combination of the flexible portion and a rigid model of the transmission system is achieved. And the natural frequency and vibration mode of the housing are obtained in the Romax Designer. The finite element calculation result is consistent with the result of modal test. The results of modal analysis can be used to the dynamic response analysis and dynamic strength design of the transmission.